Identification of 1-phenoxy-3-(piperazin-1-yl)propan-2-ol derivatives as novel triple reuptake inhibitors - Ashrafuzzaman Md.; Ji, Su Hyun; Ahn, Hyomin; Chung, Hwan Won; Choi, Daeun; Park, Ju Jin; Go, Min Ji; Pyo, Jung in; Azam Sharif Mohammed Shafioul; Lee, DuckHyung; Chi, SungGil; Song, Chiman; et al. (대한화학회, 2023)
Novel 1-phenoxy-3-(piperazin-1-yl)propan-2-ol derivatives were designed and synthesized as potential triple reuptake inhibitors, which simultaneously inhibit serotonin, norepinephrine, and dopamine transporters (SERT, NET, and DAT, respectively). Through neurotransmitter transporter uptake assays, inhibitory activities of 1-phenoxy-3-(piperazin-1-yl)propan-2-ol derivatives were evaluated. We discovered compound 19 exhibited the most potent inhibitory activities against all three monoamine neurotransmitter transporters and the IC50 values of 19 against SERT, NET, and DAT were determined. In addition, binding modes of 19 with SERT, NET, and DAT were predicted by docking studies.